Impact of a Short-Term Domestic Service-Learning Program on Medical Student Education - Brian A. Chang; Elizabeth Karin; Zachary A. Davidson; Jonathan Ripp; Rainier P. Soriano (Ubiquity Press, 2019)
Purpose: The number of global health opportunities offered to medical students has increased over the past 20 years. Recognizing the growing prevalence of these experiences, a number of studies have shown that these types of exposures have a significant impact on medical students' education. However, there is a paucity of literature on the educational impacts of short-term domestic service-learning trips, which can be more accessible due to fewer logistical and financial barriers. This mixed-methods qualitative/quantitative study aims to understand the impact of a domestic one-week service learning program on medical students' educational development and career choices. Methods: The authors conducted a qualitative analysis of journal entries written by a cohort of students during a domestic weeklong service trip. They also administered a survey to all students who had participated in the program between 2009-2016. Results: In 88.6% (n = 31) of the journal entries, students reported learning about border town life, Native American health, and rural medical practice. In 42.8% (n = 15) of entries, participants described experiences they felt would impact their future medical career decisions. The students' reflections also revealed implicit benefits such as becoming aware of privilege within society (n = 14, 40.0%). The majority of survey respondents reported that the trip improved their medical education and influenced the field and location of their future/current practice. Conclusion: This study suggests that domestic short-term service-learning trips impact medical students' immediate educational development and may influence their future career plans. Further investigation into the local community's perceptions of this service-learning trip will provide greater understanding of the impact on all involved.